Relation of Vaccination with Severity, Oxygen Requirement and Outcome of COVID-19 Infection in Chattogram, Bangladesh - Das, Shuva; Tumpa, Nadia Islam; Khan, Ayesha Ahmed; Hoque, Md. Minhazul; Hoque, Md. Ehsanul; Safatujjahan; Ahmed, Kazi Farhad; Biswas, Rajat Sanker Roy (Archives of Clinical and Biomedical Research, 2021)
Introduction: Peoples all around the world are waiting for vaccination against COVID-19 infection. In Bangladesh, Astra-Zeneca (AZ) vaccine was provided, but patients had infections of SARS-COV-2 even after vaccination. We focused on observing the severity, oxygen requirement and outcome of the COVID-19 infected patients who took the first dose or completed the immunization regimen. Methods: This is an observational study done among 174 COVID-19 patients from three COVID-19 dedicated hospitals of Chattogram, Bangladesh, who took AZ vaccines 1st dose or completed the schedule. All patients were Real-Time Reverse Transcription Polymerase Chain Reaction (rRT-PCR) positive for COVID-19. Patients were enrolled after receiving written informed consent. Suspected cases or unwilling patients were excluded from the study. Ethical approval was granted by the CMOSH–ERB. SPSS-20 was used to analyze the information gathered. Results: Among 174 vaccinated patients, 55 (31.61%) completed the vaccination schedule, and 119 (68.39%) took their 1st dose of the COVID-19 vaccine. Gender distributions revealed 67 (38.5%) female and 107 (61.5%) male got the vaccine, and 55 patients completed the full two doses, and 119 patients took the 1st dose. Most of the patients were 40 years and above. In the completed vaccination group, 33 (60.0%) out of 55 in and in the first dose vaccinated group, 75 (63.0%) out of 119 had a mild COVID-19, and severe and critical cases were found very minimum. Among the patients who have completed the vaccination, 32 (58.2%) needed no oxygen, and who was given the first dose, 78 (65%) needed no oxygen. No death occurred who completed the vaccine, and 3 (2.5%) patients died who took 1st dose of the vaccine. Conclusion: Vaccine provided in Bangladesh to the people so far seems safe and effective. Severe and critical CO